Changes in Dendritic Architecture: Not Your “Usual Suspect” in Control of the Onset of Puberty in Male Rats - Hemond, Peter; O'Boyle, Michael; Gay, Vernon; Hemond, Zoe; Suter, Kelly (Frontiers in Endocrinology, 2013)
Until the recent past, the search for the underlying drive for the pubertal increase in gonadotropin-releasing hormone (GnRH) hormone from the GnRH-containing neurons in the hypothalamus was largely focused on extrinsic factors. The most recent evidence however indicates changes in the structure of GnRH neurons themselves may contribute to this fundamental event in development. Based on our studies in males, dendritic architecture is not static from birth until adulthood. Instead, dendrites undergo a dramatic remodeling during the postnatal period which is independent of testosterone and occurs before the pubertal increase in GnRH release. First, the number of dendrites emanating from somata is reduced between infancy and adulthood. Moreover, a dendrite of adult GnRH neurons invariability arises at angle of 180° from the axon as opposed to the extraordinary variability in location during infancy. In fact, in some neurons from infants, no dendrite even resides in the adult location. Thus, there is a spatially selective remodeling of primary dendrites. Secondly, dendrites of GnRH neurons from infants were highly branched prior to assuming the compact morphology of adults. Finally, other morphological aspects of GnRH neurons such as total dendritic length, the numbers of dendrite branches and the lengths of higher order branches were significantly greater in infants than adults, indicating a consolidation of dendritic arbors. Activity in multi-compartment models of GnRH neurons, suggest the impact of structure on neuronal activity is exerted with both active and passive dendrites. Thus, passive properties make a defining contribution to function. Accordingly, changes in morphology alone are likely to have functional consequences for the pattern of activity in GnRH neurons. Our findings suggest structural remodeling of dendrites during the postnatal period likely facilitates repetitive action potentials and thus, GnRH release at the time of puberty.